Biometric Pilot-Studies Reveal the Arrangement and Shape of Windows on a Traditional Façade to be Implicitly “Engaging”, Whereas Contemporary Façades are Not - Nikos A. Salingaros; Ann Sussman (Urban Science, 2020)
The human brain evolved to implicitly approach or avoid objects in its surroundings. Requisite for survival, this behavior happens without conscious awareness or control, honed over 60 million years of primate evolution. Biometric technologies, including eye tracking, reveal these unconscious behaviors at work and allow us to predict the initial response of a design experience. This paper shows how a biometric tool, 3M-VAS (Visual Attention Software), can be effectively used in architecture. This tool aggregates 30 years of eye-tracking data, and is commonly applied in website and signage design. A pilot-study uses simplified drawings of building elevations to show 3M-VAS’s predictive power in revealing implicit human responses of engagement and disengagement to buildings. The implications on the impact of a structure in creating the public realm suggest recommendations for approving new architecture.